Head and Neck Reconstruction by Using Extended Pectoralis Major Myocutaneous Flap - Onoda, Satoshi; Azumi, Shogo; Miura, Yuki; Kimata, Yoshihiro (Journal of Reconstructive Microsurgery, 2015)
Background Pectoralis major flaps have been the workhorse in head and neck region reconstructions till date. However, pectoralis major flaps have disadvantages, including limitations regarding flap range and less stable blood flow than that in free flaps. Here, we report on the safe reconstruction to the oral cavity and neck area by using extended pectoralis major flaps. These flaps include both the normal vessels that feed pectoralis major flaps (the thoracoacromial artery and vein) and the lateral thoracic artery and vein to stabilize blood flow and expand flap survival area caudally.Methods Eight patients who had undergone reconstruction with extended pectoralis major flaps after the resection of head and neck cancers from June 2009 to March 2013. In all cases, the pectoralis major flap was elevated with a vascular pedicle comprising the thoracoacromial artery and vein and the lateral thoracic artery and vein.Results No blood circulation disorders, such as ischemia or congestion, were observed after the flaps were elevated and moved to the resected areas. All flaps were sutured on without difficulty. The area the flaps were harvested from was closed in a single stage. No postoperative complications such as hematoma, abscess, or fistula were observed.Conclusion Extended pectoralis major flaps have a wide range and more stable blood flow, so they are thought to be useful in situations in which free flaps cannot be used for a variety of reasons.
Keywords: pectoralis major myocutaneous flap; thoracoacromial vessels; lateral thoracic vessels